1996
DOI: 10.1095/biolreprod54.5.1025
|View full text |Cite
|
Sign up to set email alerts
|

Progestin-Induced Puberty and Secretion of Luteinizing Hormone in Heifers1

Abstract: Two experiments were designed to investigate the endocrine mechanisms by which progestin administration induces puberty in heifers. In experiment 1, prepubertal heifers were randomly assigned by age to receive either a single norgestomet implant for 10 days (NORG; n = 15) or to serve as unimplanted controls (CONT; n = 14). Serial blood samples were obtained on Days -0.5, 8.5, and 10.5 (Day 1 = day of implant insertion) and were analyzed for concentrations of LH. On days 9 and 11, 4 heifers in each treatment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
34

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 21 publications
2
31
0
34
Order By: Relevance
“…Concentrations of progesterone in plasma were determined in duplicate using a double-antibody RIA (Anderson et al 1996). The intra-assay CV was 3.4% and the inter-assay CV (three assays) was 14.9% for standard pools containing 1.4 and 6.9 ng ml 21 progesterone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of progesterone in plasma were determined in duplicate using a double-antibody RIA (Anderson et al 1996). The intra-assay CV was 3.4% and the inter-assay CV (three assays) was 14.9% for standard pools containing 1.4 and 6.9 ng ml 21 progesterone.…”
mentioning
confidence: 99%
“…Concentrations of oestradiol in plasma were determined in duplicate using a double-extraction single-antibody RIA (Anderson et al 1996). The antibody used (Dr N R Mason, Lilly Research Laboratories, Indianapolis, IN, USA) has a 71% cross-reactivity with ODB (Kesler et al 1977).…”
mentioning
confidence: 99%
“…Concentrations of E 2 in follicular fluid were measured using a single-antibody RIA procedure routinely employed in our laboratory for measuring E 2 in serum or plasma (Anderson et al 1996). This assay was modified by increasing the range of standard concentrations (2-2000 pg/ml) and using samples directly (without extraction of lipids).…”
Section: Ria Of Ementioning
confidence: 99%
“…Anderson et al (1996) supposes that exogenous progesterone reduces the number of hypothalamic estradiol receptors, resulting in increased frequency of LH pulses after the end of treatment with P4. Day et al (1987) observed that the cytosolic concentration of estradiol receptors on the anterior and medial basal hypothalamus and anterior pituitary reduced linearly as puberty approached.…”
Section: Peripheral Concentration and The Pulses Frequency Of Luteinimentioning
confidence: 99%
“…Several studies demonstrated that the use of progesterone may advance puberty in heifers (GONZALEZ-PADILLA, 1975;ANDERSON, et al 1996;CLARO JR, et al 2010). …”
Section: Introductionmentioning
confidence: 99%